Conductivity study in PEO-LiOAc based polymer electrolyte - Majid, Siti Rohana; Arof, Abdul Kariem; Ismail, L. (Springer Verlag (Germany), 2009)
Polyethylene oxide (PEO) films doped with lithium acetate (LiOAc) were prepared by the solution cast technique. The molecular weight of PEO was 300 000 g mol(-1). Lithium acetate was added to PEO in different weight ratios ranging from 0 to 30 wt-%. The PEO-LiOAc mixtures were dissolved in 1% acetic acid solution and stirred overnight. The highest electrical conductivity obtained for this system is 2.18 x 10(-6) S cm(-1) for the sample containing 30 wt-% CH(3)COOLi. The conductivity-temperature study was carried out for all samples from 25 to 100 degrees C. Different amounts of ethylene carbonate were added as a plasticiser. This resulted in the conductivity increasing to 1.46 x 10(-5) S cm(-1).